Chitosan elicitation and sequential Diaion® HP-20 addition a powerful approach for enhanced plumbagin production in Plumbago indica root cultures. (February 2017) - Jaisi, Amit; Panichayupakaranant, Pharkphoom
Graphical abstract: Highlights: 72 h chitosan elicitation at 14 days significantly increased plumbagin production. Sequential addition of Diaion ® HP-20 after chitosan elicitation improved production. Productivity of 19.93 mg g −1 DW was 10-fold of the control cultures within 17-days. Abstract: Plumbago indica L. is an important source of plumbagin, a bioactive naphthoquinone known for its potent anticancer and antimicrobial properties. However, due to its low supply, this work aimed to enhance the production of plumbagin using root cultures of P. indica through the combined action of chitosan elicitation and in situ adsorption using a nonpolar copolymer adsorbent, styrene-divynilbenzene resin (Diaion ® HP-20). Treatment with chitosan at concentrations of 150 mg L −1 to 14 days old culture for 72 h markedly increased the production of plumbagin [13.08 mg g −1 dry weight (DW)] by up to 6.6-fold compared to the level of an untreated root culture (1.97 mg g −1 ). The sequential addition of Diaion ® HP-20 (10 g L −1 ) to the root cultures after the chitosan treatment for 48 h markedly increased the plumbagin production up to 19.93 mg g −1 DW, which was 1.2- and 10-fold higher than the chitosan treated and untreated root cultures respectively. These results indicated that the chitosan elicitation and sequential addition of Diaion ® HP-20 was a powerful approach for increasing the production of plumbagin, and thus this key strategy with P. indica root cultures may be considered for development as a commercialized method for production of plumbagin.